If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -7x = 35 Reorder the terms: -7x + 3y = 35 Solving -7x + 3y = 35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. -7x + 3y + -3y = 35 + -3y Combine like terms: 3y + -3y = 0 -7x + 0 = 35 + -3y -7x = 35 + -3y Divide each side by '-7'. x = -5 + 0.4285714286y Simplifying x = -5 + 0.4285714286y
| y=(3)(-2)-4 | | -4.5+x=14.5 | | 25+1=7x+37 | | 2(3+5)=4 | | 8x+5=-27 | | -56+23= | | 12x+12=10x+6 | | -146+(-98)= | | 3.4(0.03)= | | 2x+1=12x-6 | | -20x^3-4x^2= | | 3x+7=n | | =64x^3-125 | | 34-(-18)= | | -5.4(2t+6)-1.8(3t-5)= | | -2x=-8-4x | | Y=8+63 | | 115-7x=11x+23 | | 9x+19*5=9x+19+119 | | =x^4-16 | | 3=22-5 | | -22-4=8-7x | | 9-8x=54-29x | | Y=46-12 | | 4x+5=19-8x | | 19m-3=7m | | 2(x+7)(x-3)=x(x+7)+90 | | Y=34+8 | | -50-7x=10x+8 | | -31x-2x=14-7x | | -31-3x=7x+21 | | 5y-6+y+42=6y+40-4y |